PERAN POLISI WANITA ( POLWAN ) DALAM ERA DIGITAL - Tri Prasetijowati; A.Hafizh Maulana; Diana Eka Agustin (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
Women Police (Polwan) are an important part of the Police institution, Women Police (Polwan) in carrying out their duties have a strategic role and function, namely as law enforcers, protectors in providing protection, and providing services to the community in realizing security and public order. In the digital era, female police (Polwan) are urgently needed to address the problem of massive social media content onto digital platforms. In this writing used the method of literature review. The results of the analysis of the study show that the role of female police officers (Polwan) in the digital era, in addition to the main duties of law enforcers, is also the main actor in filling out social media content as a means of educating legal awareness in order to create public security and order. And to carry out the dual role absolutely female police (Polwan) must have qualified digital literacy skills.